Competitiveness of the South Africa citrus fruit industry relative to it's Southern Hemisphere counterparts from 1989 to 2019 - Mokonyane, Lefa Given (My University, 2024)
The citrus fruit industry holds a significant position within South Africa's agricultural sector due to its labour-intensive and export-oriented practices. However, this industry faces growing competition not only on a global scale but particularly from citrus fruit producers in the Southern Hemisphere. The Southern Hemisphere counterparts benefit from similar climatic conditions and have access to the same export markets. Thus, the objective of this study was to compare and analyse the competitiveness of South Africa's citrus fruit industry with its counterparts in the Southern Hemisphere from 1989 to 2019. To conduct this analysis, annual time series data was collected from reputable sources such as the Food and Agricultural Organisation of the United Nations and the International Trade Centre (ITC). The data was analysed using Microsoft Excel spreadsheet and Eviews 12 software. The Balassa Revealed Comparative Advantage (RCA) index and the Net Export index (NXI) were employed as measures to assess the competitive performance of South African citrus fruit in comparison to its Southern Hemisphere counterparts. The competitiveness of different South African citrus fruits in major markets was analysed using the Constant Market Share (CMS) model. Additionally, the Armington model was utilized to examine the macroeconomic factors that impact the competitiveness of the South African citrus industry. The findings from the Balassa Revealed Comparative Advantage (RCA) index indicated that the South African citrus industry demonstrates a stronger and relatively higher competitive advantage in the production and exportation of most citrus fruit product categories compared to its Southern Hemisphere counterparts. The results from the Net Export index align with the RCA findings, showing that South Africa is a net exporter of citrus fruits. Moreover, the CMS results shed light on the pecific markets where different citrus fruits exhibit competitiveness. Lastly, this study identified various macroeconomic factors, both in the short and long run, that influence the competitiveness of the South African citrus industry at different levels of significance. For the industry to be sustainable and to enhance its competitiveness, several recommendations and strategies are suggested at the end of this study which includes exploring potential strategic markets like the Russian and the Asian market, reducing reliance on the EU and producing and exporting more lemons and limes; and soft citrus.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Citrus fruit industry; Net Export index; Armington model; Constant Market Share; Revealed comparative advantage; Citrus juice industry; Citrus fruit industry; Citrus